Strategi Adaptasi dalam Komunikasi Antarbudaya (Kajian Literatur Tentang Perspektif Teori dan Praktik) - Exsan Adde (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
Intercultural communication has become increasingly important in the era of internationalization, marked by the high intensity of cross-cultural interactions. This article examines adaptation strategies in intercultural communication through a literature review approach, highlighting key theories such as Communication Accommodation Theory (CAT), Cultural Adaptation Model, and Uncertainty Reduction Theory (URT). The findings of this literature review emphasize that successful adaptation in intercultural contexts requires the development of cultural awareness, comprehensive communication skills (verbal, vocal, and nonverbal), and cultural empathy, which serve as coping mechanisms and facilitators of interaction. URT provides a strategic framework through passive, active, and interactive approaches to reduce uncertainty in intercultural relationships. Furthermore, the concept of intercultural competence proposed by Slocum and Hellriegel underscores the importance of integrating intellectual capacity, personal character, and practical skills. This article makes a theoretical contribution by synthesizing various perspectives on intercultural adaptation and offering practical implications for multicultural education and relationship management in plural societies, without proposing a new empirical model but instead reinforcing existing conceptual frameworks.